Influence of Diatomite and Mineral Powder on Thermal Oxidative Ageing Properties of Asphalt - Yongchun Cheng; Jinglin Tao; Yubo Jiao; Qinglin Guo; Chao Li (Advances in Materials Science and Engineering)
Ageing of asphalt affects the performances of asphalt pavement significantly. Therefore, effects of diatomite and mineral powder on ageing properties of asphalt were investigated systematically in order to improve the antiageing property of mixture. Thin film oven test (TFOT) was used to conduct the short term ageing in laboratory. Softening points, penetrations, force ductility, low temperature creep properties, and viscosities of asphalt mastics were tested before and after TFOT, respectively. Results indicated that percent retained penetration (PRP) increased with the increasing of fillers. Increment of softening point (ΔT), ductility retention rate (DRR), deformation energy ageing index (JAI), and viscosity ageing index (VAI) of asphalt mastics nonlinearly decreased with the increasing of fillers. Ageing of asphalt was reduced by diatomite and mineral powder. And the antiageing effect of diatomite was better than that of mineral powder as a result of its porous structure. It is suggested that the mineral powder could be reasonably replaced by diatomite in order to reduce thermal oxidative ageing of asphalt mixture. The optimal content of diatomite 12.8% is also suggested for engineering.